ANALISIS TANTANGAN FISIK DAN SOSIAL DALAM PENGELOLAAN LINGKUNGAN BELAJAR DI SEKOLAH - Murti, Krisna Bayu; Putri, Fazaisya Zuhrianggi (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2025)
Learning environment management plays an important role in creating a conducive atmosphere and supporting student development. However, teachers often face challenges from both physical and social aspects. This article examines two cases, namely limited school land that hinders outdoor learning and bullying that disrupts the classroom social climate. The study employed a descriptive qualitative approach with a case study method. The analysis shows that limited land requires teachers to be more creative through strategies such as rotation, the use of traditional games, and multifunctional spaces to ensure outdoor learning activities continue. Meanwhile, bullying highlights the teacher’s role in fostering positive social interactions, enforcing classroom rules, and involving parents and schools. These cases demonstrate that learning environment management is not only determined by physical facilities but also by the quality of social relationships. With teacher creativity and collective support, challenges can be overcome to create a safe and meaningful learning environment.